2010
DOI: 10.1186/1746-1340-18-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of manual therapies: the UK evidence report

Abstract: BackgroundThe purpose of this report is to provide a succinct but comprehensive summary of the scientific evidence regarding the effectiveness of manual treatment for the management of a variety of musculoskeletal and non-musculoskeletal conditions.MethodsThe conclusions are based on the results of systematic reviews of randomized clinical trials (RCTs), widely accepted and primarily UK and United States evidence-based clinical guidelines, plus the results of all RCTs not yet included in the first three catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
254
2
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(284 citation statements)
references
References 245 publications
7
254
2
13
Order By: Relevance
“…We used criteria for determining strength of evidence modified from that described in the UK report 20,21 and detailed in Table 1: high quality, positive or negative; moderate quality, positive or negative; and inconclusive, favorable or unfavorable.…”
Section: Strength Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…We used criteria for determining strength of evidence modified from that described in the UK report 20,21 and detailed in Table 1: high quality, positive or negative; moderate quality, positive or negative; and inconclusive, favorable or unfavorable.…”
Section: Strength Of Evidencementioning
confidence: 99%
“…14 For SIS, 2 reviews 95,96 reported that MT combined with exercise was effective. Bronfort et al 20 concluded that combining MT with medical care was beneficial, and another review 97 found evidence to suggest massage was superior to no treatment. Our results contrasted with several reviews that reported that passive therapies such as LLLT and PEMF were not effective or that results were inconclusive for the treatment of RCs, AC, and SIS.…”
Section: Nonspecific Spmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] The scientific evidence on SMT for the relief of chronic LBP has been well discussed in systematic reviews. 22,23 Previously reported data for our trial showed a sustainable within dose-group treatment effect across multiple dose groups to 52 weeks and, while 12 SMT visits were favored, this was not well distinguished from 6 and 18 visits. 24 The purpose of this analysis is to report the incremental cost of treatment and lost productivity as well as the benefit in terms of pain-free and disability-free days.…”
Section: Introductionmentioning
confidence: 99%
“…An article by Cassidy and colleagues, ''Risk of vertebrobasilar stroke and chiropractic care: results of a population-based case control and case-crossover study,'' received 11 submissions as essential literature for chiropractors. 7 Second in ranking was Bronfort et al, 8 ''Effectiveness of manual therapies: the UK evidence report.'' Five articles received 3 recommendations: ''A theoretical model for the development of a diagnosis-based clinical decision rule for the management of patients with spinal pain'' (Murphy 9 ), ''Clinical effectiveness of manual therapy for the management of musculoskeletal and non-musculoskeletal conditions: a systematic review and update of the UK evidence report'' (Clar et al .…”
Section: Literature With Multiple Recommendationsmentioning
confidence: 99%